Efficacy of different accelerated corneal crosslinking protocols fix progressive keratoconus - TOKER, AYŞE EBRU; ÇERMAN, EREN (ELSEVIER SCIENCE INC, 2017)
Purpose: To evaluate the efficacy of different accelerated corneal crosslinking (CXL) treatment protocols in patients with progressive keratoconus. Setting: Marmara University School of Medicine, Istanbul, Turkey. Design: Retrospective case series. Methods: Patients with progressive keratoconus had 9 mW accelerated CXL (10 minutes; 9 mW/cm(2)), 30 mW continuous light accelerated CXL (4 minutes; 30 mW/cm(2)), or 30 mW pulsed-light accelerated CXL (8 minutes [1 second on/1 second off]; 30 mW/cm(2)). Results: Of 134 eyes, 34 eyes had conventional CXL, 45 had 9 mW accelerated CXL, 28 had 30 mW continuous-light accelerated CXL (4 minutes, 30 mW/cm2), and 27 eyes had 30 mW pulsed-light accelerated CXL. The uncorrected (UDVA) (P <.001 both) and corrected (CDVA) distance visual acuities increased in with conventional CXL and 9 mW accelerated CXL (P =.001 and P =.002, respectively). With 30 mW continuous accelerated CXL, only CDVA improved (P =.019). With 30 mW pulsed accelerated CXL, UDVA and CDVA did not change significantly (P >.05). With conventional CXL and 9 mW accelerated CXL, all keratometric (K) readings (K1, K2, mean K, maximum K) improved significantly (conventional CXL: P =.014, P =.002, P =.008, and P <.001, respectively; 9 mW accelerated CXL: all P <.001). With 30 mW, no K values changed significantly compared with baseline (all groups P >.05). Conclusion: Although 30 mW accelerated CXL treatment modalities appeared to be effective in stabilizing keratoconus progression, they seemed less effective in achieving topographic improvement. (C) 2017 ASCRS and ESCRS
Keywords: RANDOMIZED CONTROLLED-TRIAL; DEMARCATION LINE; RIBOFLAVIN; STANDARD; OUTCOMES; ULTRAVIOLET; MICROSCOPY; RADIATION; FLUENCE; SAFETY